Perbandingan Tinngkat Kebugaran Jasmani Antara SMA 2 Kabupaten Solok Dengan SMA 3 Kota Padang - Wiro Pranata Yuanda; Didin Tohidin (JURNAL STAMINA, 2019)
This research originated from the researchers' curiosity regarding the level of physical fitness between of students of SMAN 2 Solok district with SMAN 3 Padang city. The purpose of this study is to compare the level of physical fitness students of SMAN 2 Solok district with SMAN 3 Padang city. The type of research used is Comparative. The population in this study were all students of SMAN 2 Solok district who were enrolled in the 2018/2019 school year as many as 175 students and students of SMAN 3 Kota Padang totaling 268 students. So the total population in this study was 443 students. Sampling uses purposive sampling techniques, so, the sample in this study was 88 students. Data was collected using the Indonesian Physical Fitness Test (TKJI). Data analysis and hypothesis testing using comparative analysis techniques. The results of data analysis using the t test obtained t count> t table, namely 7.90> 1.662. The results of this study prove that there are differences in the level of physical fitness of students of SMAN 2 Solok Regency with SMAN 3 Padang. In this case, the level of physical fitness of students at SMAN 2 Solok Regency is better than the level of physical fitness of students of SMAN 3 Padang